Phenotypic and Genetic Complexity in Pediatric Movement Disorders - Kim, Min-Jee; Yum, Mi-Sun; Seo, Go Hun; Ko, Tae-Sung; Lee, Beom Hee (Frontiers in Genetics, 2022)
The complex and evolving nature of clinical phenotypes have made genetically diagnosing pediatric patients with movement disorders difficult. Here, we describe this diverse complexity in the clinical and genetic features of a pediatric cohort examined by whole-exome sequencing (WES) and demonstrate the clinical benefit of WES as a diagnostic tool in a pediatric cohort. We evaluated 382 children with neurodevelopmental symptoms were evaluated by WES. Overall, 75 patients had diverse single or combined movement phenomenologies. WES identified 42 variants in 37 genes (56.0%). The detection rate was highest in patients with dystonia (84.6%), followed by ataxia (58.6%), myoclonus (50.0%), dyskinesia (50%), stereotypy (41.6%), and tremor (100%), respectively. Most genetically diagnosed patients (90.5%) were affected by other neurologic or systemic manifestations; congenital hypotonia (66.7%), and epilepsy (42.9%) were the most common phenotypes. The genetic diagnosis changed the clinical management for five patients (6.7%), including treatments targeting molecular abnormalities, and other systemic surveillance such as cancer screening. Early application of WES yields a high diagnostic rate in pediatric movement disorders, which can overcome the limitations of the traditional phenotype-driven strategies due to the diverse phenotypic and genetic complexity. Additionally, this early genetic diagnosis expands the patient’s clinical spectrum and provides an opportunity for tailored treatment.